2021
DOI: 10.33988/auvfd.714308
|View full text |Cite
|
Sign up to set email alerts
|

Marine fish parasite, Lernanthropus kroyeri (Copepoda) is a repository of Vibrio anguillarum as evidenced by Loop-Mediated Isothermal Amplification method

Abstract: Fish parasites act as a vector of other pathogenic diseases such as bacteria and virus in fish. Although it has been long known that fish parasites can act as a vector for bacterial pathogens, their role in the transmission of specific bacterial pathogens via particular parasites in the off-host stage has been neglected. The aim of the present study was to disclose that if the copepod parasite, Lernanthropus kroyeri in the off-host stage, can store up the aquatic bacterial pathogens: Aeromonas hydrophila, Phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Additionally, the copepod Caligus rogercresseyi is a vector for infectious salmon anaemia virus (Labra et al., 2020; Oelckers et al., 2014), and is suspected to be a reservoir for multiple other pathogens (Gonclaves et al., 2020). Lernanthropus kroyeri , another copepod, is a repository of the bacterium Vibrio anguillarum and could potentially act as a vector for this pathogen (Yildiz & Otgucuoglue, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the copepod Caligus rogercresseyi is a vector for infectious salmon anaemia virus (Labra et al., 2020; Oelckers et al., 2014), and is suspected to be a reservoir for multiple other pathogens (Gonclaves et al., 2020). Lernanthropus kroyeri , another copepod, is a repository of the bacterium Vibrio anguillarum and could potentially act as a vector for this pathogen (Yildiz & Otgucuoglue, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Lernanthropus kroyeri, another copepod, is a repository of the bacterium Vibrio anguillarum and could potentially act as a vector for this pathogen (Yildiz & Otgucuoglue, 2021).…”
mentioning
confidence: 99%
“…Alongside the severe damage to the gills, L. kroyeri may cause the increase in secondary infections in relation to acting as a vector for other microbial pathogens (Kotob et al, 2016;Misganaw & Getu, 2016). It has been shown that L. kroyeri in sea bass can act as a reservoir of pathogenic bacteria, Vibrio anguillarum (Yavuzcan & Otgucuoglu, 2021).…”
mentioning
confidence: 99%